Level of Project Management of Estimation, Planning and Tracking and uses techniques (International Journal of Engineering and Computer Science, 2017)
The process begins with estimating the size, effort and time required for the development of the software and ends with the product and other work products built in different phases of development. Model based technique is one of the best techniques used for estimation. Software engineering is the discipline which paves the roadmap for development within given schedule and effort and with the desired quality. The technique uses different parameters for estimation. The estimates should be accurate, failing to which leads to wrong estimates and consequently results in software crisis. The tools available for automating some of the activities are great help in the whole development process. However these tools isolate the process of estimation, planning & tracking and calibration. Secondly Software Engineering is a nascent discipline and still the metrics introduced for quantifying the attributes of software are not judgments. Handling large volume of data for these processes is a tiresome task.